Resiliensi Organisasi dan Kinerja Organisasi: Peran Kepemimpinan Resilien sebagai Mediator - Suryaningtyas, Dianawati; Wilujeng, Sri (Jurnal Ekonomi Modernisasi, 2017)
This research aims to test the relationship between organizational resilience and organizational performance, directly and indirectly through resilient leadership. Method used survey research with quantitative approach, and path analysis to analise the influence of each variable. Findings show that organizational resilience did not influenced organizational performance directly. Instead, organizational resilience significantly influenced organizational performance through resilient leadership. Respondents prefer to choose strategic organizational resilience. This indicates that organizations already reached top level of maturity. It means that in facing crisis or threats, organizations response it by doing organizational resilience with the purpose not only back to normal, but also to become thrive (bounce forwards). The findings of this research is that organizational resilience can be enhanced by using resilient leadership.